College Students’ Perception about the Implementation of Democratic and Humanist Learning Model in State Islamic Institute (IAIN) Sultan Amai Gorontalo - Siti Asiah.T; Herson Anwar (Nadwa: Jurnal Pendidikan Islam, 2018)
This research aims to analyse the perception of students of Islamic Education Management Study Program at Faculty of Teacher Training and Education, Islamic State University (IAIN) Sultan Amai Gorontalo about the implementation of democratic and humanist learning model. The sample used in the research was 98 respondents. The data analysis technique used was descriptive statistic by using Weighted Means Score (WMS) formula. The research result about student perception showed that lecturers at Islamic Education Management Study Program had already been applied democratic and humanist learning model perfectly in the interactive learning condition. To realize a democratic and humanist learning model, lecturer figure is needed that has the knowledge and ability to develop a model of democratic and humanist learning. AbstrakPenelitian ini bertujuan untuk mengkaji dan menganalisis persepsi mahasiswa Prodi Manajemen Pendidikan Islam Fakultas Ilmu Tarbiyah dan Keguruan IAIN Sultan Amai Gorontalo tentang penerapan model pembelajaran yang demokratis dan humanis. Jumlah sampel adalah 98 responden. Teknik analisis data menggunakan statistik deskriptif dengan rumus Weighted Means Score (WMS). Hasil penelitian mengenai persepsi mahasiswa menunjukkan bahwa model pembelajaran demokratis dan humanis sudah diterapkan dengan baik dalam suasana pembelajaran yang interaksi dan interaktif. Untuk mewujudkan model pembelajaran yang demokratis dan humanis, diperlukan sosok dosen yang memiliki pengetahuan dan kemampuan untuk mengembangkan model pembelajaran demokratis dan humanis